1998
DOI: 10.1677/joe.0.1590117
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relaxin, pregnancy and parturition on collagen metabolism in the rat pubic symphysis

Abstract: The aim of this study was to examine the changes in collagen metabolism that occur during pregnancy and parturition and upon relaxin administration to the rat pubic symphysial interpubic tissue. Pubic symphyses were collected from non-pregnant, and intact and ovariectomised pregnant Sprague-Dawley rats at days 15, 18 and 21 of pregnancy as well as during and after delivery, and analysed for collagen content and solubility. SDS-PAGE was used to determine collagen composition. During pregnancy and particularly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
54
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 34 publications
6
54
2
Order By: Relevance
“…The preponderance of women in the present study is consistent with previous findings (6). Attempts to explain female dominance among TMJD patients have identified several potential predisposing factors, including the effects of gonadal hormones such as estrogen, progesterone, and relaxin (17,18). These hormones are believed to have a degenerative effect on the disc and/or bone of the mandibular condyle.…”
Section: Discussionsupporting
confidence: 91%
“…The preponderance of women in the present study is consistent with previous findings (6). Attempts to explain female dominance among TMJD patients have identified several potential predisposing factors, including the effects of gonadal hormones such as estrogen, progesterone, and relaxin (17,18). These hormones are believed to have a degenerative effect on the disc and/or bone of the mandibular condyle.…”
Section: Discussionsupporting
confidence: 91%
“…This could be an effect of peri-parturient hormones, such as relaxin (Tarlton et al, 2002) or estrogens. Relaxin, for example, mediates distension of the reproductive tract for parturition by activating metalloproteinases that degrade collagen and is known to have effects on other structures throughout the body (Samuel et al, 1998); if it acts upon the suspensory apparatus it could cause the distal phalanx to sit lower in the hoof around calving. In previous work assessing the thickness of the sole soft tissues in a cross-sectional study, the nadir of sole soft tissue thickness was observed at approximately 120 DIM and corresponded with the nadir of BCS (Bicalho et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Types IX, XI, XII and XIV are fibril associated collagens with small chains, which contain some non-helical domains. Type VI is microfibrillar collagen and type VII is anchoring fibril collagen (Samuel et al, 1998). Fig.…”
mentioning
confidence: 99%